De novo proliferative glomerulonephritis with monoclonal IgG deposits of the IgG1κ subtype in a kidney allograft. (July 2016) - Tsuji, Takahiro; Miura, Masayoshi; Yanai, Mitsuru; Itami, Hiroe; Ishii, Yasushi; Akimoto, Mayuko; Fukasawa, Yuichiro
Abstract: Proliferative glomerulonephritis with monoclonal immunoglobulin G (IgG) deposits (PGNMID) has recently been described in cases with glomerular disease. Only 16 cases of recurrent or de novo PGNMID have been reported in the transplanted kidney. Here we report a case of de novo PGNMID in a renal allograft diagnosed in the early stage by protocol biopsy. A 41‐year‐old male with end‐stage kidney disease caused by focal glomerular sclerosis received a living‐related kidney transplant. The post‐transplantation course was stable, except for an early episode of acute T cell‐mediated rejection. Mesangial C1q deposition was found on the 3‐year protocol biopsy. On the 4‐year protocol biopsy, mild mesangioproliferative changes and deposition of IgG, C1q, C3, IgG1, and κ light chain were evident, confirming the diagnosis of PGNMID of the IgG1κ subtype. Furthermore, mild proteinuria was detected at that time. Because a subsequent haematological examination revealed high copy number Epstein–Barr virus (EBV) DNA and free κ light chain in blood, the post‐transplant lymphoproliferative disorder (PTLD) was suspected. Mycophenolate mofetil (MMF) was discontinued and rituximab was administered for the treatment of PTLD; subsequently, the improvement in proteinuria and serum creatinine was found 2 months after rituximab administration.